Estudio Analítico de la Ejecución del Plan de Mantenimiento de la Alesadora CNC DN DBC110 utilizada en la reparación de Equipos Amarillos de la Empresa ABC localizada en la ciudad de Soledad. - Bello Lozano, Vanessa Aurora; Rueda Quintero, Euclides (Universidad Antonio Nariño, 2023)
As a first half in the first objective when collecting information about the current process and fundamental sections of the DN DBC110 CNC Boring Machine, information from primary sources, plans and maintenance records were taken into account, giving clarity to the research approach.